2010
DOI: 10.1111/j.1443-1661.2010.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy With and Without Abdominal Prophylactic Drainage

Abstract: The use of drain after simple elective uncomplicated LC could safely be limited to appropriate patients as judged by the operating surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
4
8
0
1
Order By: Relevance
“…The surgeon performs drain insertion with the expectation that drainage would be helpful for detecting bleeding or bile leak with a color change or a rapid increase in drained fluid in the early postoperative period and that drainage would be effective in preventing the formation of hematoma or biloma. However, several recent studies have reported opposite results . This experimental study showed that the lumen of the inserted drain is quickly surrounded and completely occluded by omental tissue within 48 h and then loses the function of detection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The surgeon performs drain insertion with the expectation that drainage would be helpful for detecting bleeding or bile leak with a color change or a rapid increase in drained fluid in the early postoperative period and that drainage would be effective in preventing the formation of hematoma or biloma. However, several recent studies have reported opposite results . This experimental study showed that the lumen of the inserted drain is quickly surrounded and completely occluded by omental tissue within 48 h and then loses the function of detection.…”
Section: Discussionsupporting
confidence: 83%
“…Because the incidence of these complications is relatively rare, it is expected that the clinical significance of drainage would be very low. Furthermore, some authors assert that the drain can facilitate the bile leak from the superficial bile ductules due to the mechanical irritation from foreign materials of the drain itself, the sucking effect of a closed drain, and the creation of dead space [10,12]. Drains have also been used to remove remnant infectious debris or fluid and to prevent the formation of an intraabdominal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…According to Julio and Ishikawa's research the length of hospital stay is shorter when drainage is abandoned [16–18]. Our study also confirmed the shorter hospital stay of patients without drainage.…”
Section: Discussionsupporting
confidence: 83%
“…In Piotr's series, infectious complications were observed in 10% of the patients who had drainage after splenectomy. The Authors reported a shorter hospital stay in patients without drainage (6), data which is confirmed also by other surgeons (29)(30)(31)(32). Accordingly, Cohn (13) found a ten-fold increased risk of infectious complications in the splenic fossa, an increased risk which was observed also by Cherise et al (14).…”
Section: Discussionsupporting
confidence: 76%